2016
DOI: 10.1093/jb/mvw076
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of the flagellar stator-associated inner membrane protein FliL fromVibrio alginolyticus

Abstract: The flagellar motor is embedded in the cell envelope and rotates upon interaction between the stator and the rotor. The rotation is powered by ion flow through the stator. A single transmembrane protein named FliL is associated with torque generation in the flagellar motor. We established an Escherichia coli over-expression system for FliL of Vibrio alginolyticus, a marine bacterium that has a sodium-driven polar flagellum. We successfully expressed, purified, and crystallized the ca. 17 kDa full-length FliL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The particle weight value estimated from the mobility of the gel-filtration column calibrated using globular proteins of a known mass gave the value of approximately 11.2 kDa, which suggested that H. pylori FliL-C is monomeric in solution under the tested conditions. This result is in agreement with the previous report on the periplasmic domain of Vibrio alginolyticus FliL, which is also primarily monomeric in solution in the concentration range used in this study (27).…”
Section: Crystallizationsupporting
confidence: 94%
See 1 more Smart Citation
“…The particle weight value estimated from the mobility of the gel-filtration column calibrated using globular proteins of a known mass gave the value of approximately 11.2 kDa, which suggested that H. pylori FliL-C is monomeric in solution under the tested conditions. This result is in agreement with the previous report on the periplasmic domain of Vibrio alginolyticus FliL, which is also primarily monomeric in solution in the concentration range used in this study (27).…”
Section: Crystallizationsupporting
confidence: 94%
“…However, it is anticipated that determination of the crystal structure of its soluble periplasmic domain will provide a critical insight into its function through identification of functional homologues with a similar fold, as protein structure is more conserved than sequence. The production of the crystals of the periplasmic domain of FliL from Vibrio alginolyticus was reported (27), but no structure is available yet. Here, we report the cloning, purification, crystallization and the preliminary X-ray crystallographic analysis of the C-terminal periplasmic domain of H. pylori FliL.…”
Section: Introductionmentioning
confidence: 99%
“…Since the protein diffusion on membrane usually dominated by the number of transmembrane segment 56 , it’s unusual to measure such a low diffusion rate for a single transmembrane FliL protein. According to the recent biochemical characterization 57 , FliL without transmembrane domain would interact with each other to form oligomer. These results highly suggest that FliL protein may diffuse on the membrane as an oligomer.…”
Section: Discussionmentioning
confidence: 99%
“…The motor of this spirochete also possesses a particular structure, called the collar, to which FliL is associated (18). Furthermore, biochemical and X-ray crystallography studies in V. alginolyticus suggested that rings of FliL might associate around stator units (19,20). From these and other studies, it may be concluded that FliL is a small membrane protein that is part of the flagellar basal body and that might have a role in stabilizing the stator (21).…”
mentioning
confidence: 90%
“…In addition to the paucity of studies on the role of FliL in alphaproteobacteria, there are no comparative works in bacterial species possessing two flagellar systems except for recent studies in V. alginolyticus (19,20). Since B. diazoefficiens uses its two flagellar systems for swimming (2), this species brings an opportunity to compare the role of FliL in each system for swimming.…”
mentioning
confidence: 99%